2017
DOI: 10.1148/rg.2017170077
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning: A Primer for Radiologists

Abstract: Deep learning is a class of machine learning methods that are gaining success and attracting interest in many domains, including computer vision, speech recognition, natural language processing, and playing games. Deep learning methods produce a mapping from raw inputs to desired outputs (eg, image classes). Unlike traditional machine learning methods, which require hand-engineered feature extraction from inputs, deep learning methods learn these features directly from data. With the advent of large datasets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
667
0
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 924 publications
(687 citation statements)
references
References 35 publications
2
667
0
18
Order By: Relevance
“…The encoder-decoder networks are widely used in modern semantic and instance segmentation models [1], [2], [3], [4], [5], [6]. Their success is largely attributed to their skip connections, which combine deep, semantic, coarse-grained feature maps from the decoder sub-network with shallow, lowlevel, fine-grained feature maps from the encoder sub-network, and have proven to be effective in recovering fine-grained details of the target objects [7], [8], [9] even on complex background [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…The encoder-decoder networks are widely used in modern semantic and instance segmentation models [1], [2], [3], [4], [5], [6]. Their success is largely attributed to their skip connections, which combine deep, semantic, coarse-grained feature maps from the decoder sub-network with shallow, lowlevel, fine-grained feature maps from the encoder sub-network, and have proven to be effective in recovering fine-grained details of the target objects [7], [8], [9] even on complex background [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that large-scaled datasets for general purpose have been annotated though crowdsourcing (i.e., outsourcing of the annotation tasks to a variety of competent sources) to 40 generate ground-truth labeled ones. In healthcare, to date, though crowdsourcing has shown high potentials, such as optimizing treatment plans, predicting disease outbreaks, patient centered price transparency (Meisel et al, 2016) and drug discovery (Lessl et al, 2011), few work is initiated to annotate the medical images by crowdsourcing since outsourcing of the medical annotation work to non-expertise would lead to misclassifications (Chartrand et al, 2017;Weese and Lorenz, 2016;Zygmont et al, 2016). Some steps in this direction could be referred to the work by Albarqouni et al (Albarqouni et al, 2016).…”
Section: Crowdsourcing To Build Ground-truth Labeled Datasetmentioning
confidence: 99%
“…At the same time, the groundbreaking performance of convolutional neural networks in computer vision such as ImageNet has led to a rapid ascent of interest in the application of deep learning to medical imaging . In cases where the sample size is small, deep learning can be used for representation learning.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] At the same time, the groundbreaking performance of convolutional neural networks in computer vision such as ImageNet 16 has led to a rapid ascent of interest in the application of deep learning to medical imaging. 17,18 In cases where the sample size is small, deep learning can be used for representation learning. The key idea is to use the CNN to infer suitable feature representation for an objective task (e.g., classification) rather than to perform an end-to-end classification.…”
Section: Introductionmentioning
confidence: 99%